2003
DOI: 10.1590/s1413-78522003000400005
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da regeneração nervosa em nervos tibiais de ratos wistar utilizando o Fluoro-Gold® como marcador neuronal

Abstract: RESUMOOs autores estudaram em ratos a regeneração nervosa no enxerto nervoso tradicional, comparando-os com grupo controle, através da contagem no nível da medula espinhal, entre L3 e S1, de motoneurônios marcados por meio de exposição do nervo tibial ao Fluoro-Gold ® (FG) INTRODUÇÃOAs lesões do sistema nervoso periférico têm sido alvo de inúmeros estudos para compreensão e entendimento do pro- SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
1
0
2
Order By: Relevance
“…The fibroblasts growth factor has shown to be quite promising, having shown similar or even superior results compared to traditional nerve graft (24) . In our study, we found better results than with the use of nerve fragments, but when we compare the number of cells counted in each rat to other studies using the same methodology, we can see that the autologous nerve graft actually promotes a better peripheral nerve regeneration (25) . Since neurokins were first reported, new perspectives emerged for improving nervous regeneration; however, to date, none of these factors enabled a fully satisfactory neuronal growth.…”
Section: Discussionsupporting
confidence: 39%
“…The fibroblasts growth factor has shown to be quite promising, having shown similar or even superior results compared to traditional nerve graft (24) . In our study, we found better results than with the use of nerve fragments, but when we compare the number of cells counted in each rat to other studies using the same methodology, we can see that the autologous nerve graft actually promotes a better peripheral nerve regeneration (25) . Since neurokins were first reported, new perspectives emerged for improving nervous regeneration; however, to date, none of these factors enabled a fully satisfactory neuronal growth.…”
Section: Discussionsupporting
confidence: 39%
“…Ideally, complete function is restored by matching the regenerating axon to the same type of end organ to which it was previously connected. However, this is usually not possible, even with the use of microsurgery techniques, due to a large loss in sensory and motor neurons, mismatch between sensory and motor fibers, and topographic changes in the target organs (Brushart, 1991;Grecco et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…2), contudo, secções de fibras nervosas delgadas foram observadas centralmente em ambas as técnicas. O tecido nervoso periférico possui grande capacidade regenerativa (Stopiglia et al, 1998;Grecco et al, 2003), tornando plausível a hipótese de regeneração em cavalos submetidos à neurectomia. Um estudo retrospectivo realizado por Jackman et al (1993) relatou que 74% dos cavalos não apresentaram claudicação um ano após as cirurgias e apenas 63% deles não apresentavam sinais de dor após dois anos, sugerindo maior regeneração nervosa com o passar do tempo.…”
Section: Resultsunclassified
“…Esse procedimento, apesar de não impedir o progresso da doença, melhora substancialmente a qualidade de vida do animal e aumenta sua vida útil (Jackman et al, 1993;Turner et al, 1995). Diversas técnicas vêm sendo desenvolvidas com o intuito de minimizar as complicações pós-cirúrgicas, como a dessensibilização incompleta da área afetada, a regeneração do segmento do nervo retirado e a formação de neuromas dolorosos (Schneider et al, 1985;Cummings et al, 1988;Haugland et al, 1992;Dabareiner et al, 1997). Dabareiner et al (1997) compararam a técnica de guilhotina com diferentes técnicas de laser por CO 2 e relataram a formação de neuromas dolorosos em todos os casos, sendo a técnica de guilhotina a que produziu menores complicações pós-operatórias.…”
Section: Introductionunclassified